Peran Media Sosial Dalam Membangun Kerukunan Umat Beragama - Latip Kahpi Nasution (Hikmah, 2019)
AbstractThis study aims to understand how the role of social media in building religious harmony. The development of the digitalization era now allows everyone to convey information including the issue of religious harmony. The use of social media has a good impact on religious harmony when interpreted as a unifying media between religious communities. But on the contrary, social media can also be a cause of divisions between religious communities. For this reason, social media as a product of civilization must be used in a civilized manner so that its usefulness can be felt by the whole community, especially among religious communities. Advances in technology should be a solution to the difficulty of getting information, so that it can be a media of checks and blance on various issues in religious harmony.Keywords: Social Media, Harmony, Religious People. AbstrakKajian ini bertujuan untuk memahami bagaimana peran media sosial dalam membangun kerukunan umat beragama. Perkembangan era digitalisasi saat ini memungkinkan setiap orang untuk menyampaikan informasi termasuk isu kerukunan umat beragama. Penggunaan media sosial memberikan dampak yang baik kepada kerukunan umat beragama ketika dimaknai sebagai media pemersatu antara umat beragama. Namun sebaliknya, media sosial juga bisa menjadi penyebab terjadinya perpecahan antara umat beragama. Untuk itu media sosial sebagai salah satu produk dari pradaban harus digunakan secara beradab sehingga kebermanfaatannya bisa dirasakan oleh seluruh masyarakat terutama antar umat beragama. Kemajuan teknologi semestinya menjadi solusi terhadap kesulitan mendapatkan informasi, sehingga bisa menjadi media cek and blance terhadap berbagai persoalan dalam kerukunan umat beragama.Kata Kunci: Media Sosial, Kerukunan, Umat Beragama.